PARENTING CHILDREN WITH DISABILITIES: STRESS, COPING, AND SOCIAL SUPPORT - Lestari, Lesi; Sujadi, Eko (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2024)
Parents with children having disabilities face heightened parenting challenges, rendering them susceptible to stress. This study aims to analyze the experiences of parents with disabled children, focusing on parenting stress, coping mechanisms, and social support. The study included 3 parents selected through purposive sampling. Semi-structured interviews were conducted to elicit information from each participant. The analysis revealed three main themes: coping with stress, social support, and parenting stress. Findings indicate that parents of children with disabilities experience stress due to their circumstances, particularly concerning stressors like medical services, education, emotional support, and societal stigma. Moreover, their concerns about their children's future pose a challenging aspect to control. Strategies to manage their stress include concentrating on emotional regulation, problem-solving techniques, and acceptance of their situation, although a minority of participants resort to avoidance strategies. Spousal social support significantly aids them in problem resolution, with some participants highlighting support from other sources as beneficial. The study underscores the importance of enhancing counseling services within communities to assist parents of disabled children in navigating parenting challenges effectively.